The total mass and spatial–temporal variability of aerial cryosphere over the Tibetan Plateau from 2003 to 2020 - Yang, Yifan; Dou, Tingfeng; Xu, Gaojie; Xiao, Cunde (Frontiers in Earth Science, 2023)
Changes in snow, ice, and ecological system over the Tibetan Plateau (TP) are extremely sensitive to local precipitation and radiation budget, which are largely modulated by the atmospheric ice. However, how much ice is there in the atmosphere over the TP and how it is distributed are still unclear. The total mass, spatial distributions, and long-term trends of atmospheric ice over the TP were evaluated by using four sets of satellite retrieval data (Aqua, Terra, the Suomi National Polar-orbiting Partnership (Suomi NPP), and NOAA-20) and ERA5 reanalysis data from 2003 to 2020. Based on the estimations using multiple satellite datasets, we concluded that the total mass of atmospheric ice could be up to 0.26±0.03 Gt over the TP from 2013 to 2020. The spatial distributions of atmospheric ice derived from various datasets were highly consistent. In general, the southwest and northeast areas of the TP were the low-concentration areas (0.05 kg/m2 in average), while the southeast area was the high-concentration area (0.09 kg/m2 in average), and this spatial pattern was most evident in summer. The high values around (0.15 kg/m2) were centered over Linzhi and its surrounding areas. The plentiful water vapor transported by southwest summer monsoon and steep topography jointly led to rapid growth of atmospheric ice in Southeast Tibet, which was the dominant reason for the higher ice concentration in this area.